Selected therapeutic methods affecting the health and quality of life of chronically dermatologically ill people - Anna Ścisłowska-Czarnecka; Aleksandra Matuła; Aneta Bac; Amelia Lizak; Monika Wilk (Health Promotion & Physical Activity, 2020)
The skin is one of the first organs that manifest disorders of homeostasis occurring in the body. Chronic diseases that manifest themselves as skin problems are often associated with severe stress and the accompanying anxiety, uncertainty and pain, which consequently reduce the quality of patients’ lives. Both stress and dermatoses trigger a cycle of neurohormonal reactions in the body that affects the functioning of the nervous, endocrine and immune systems. The data presented in this article indicate a relationship between stress, the functioning of the immune system and the quality of life of patients with chronic dermatological diseases. The article stresses the necessity of a holistic approach to skin problems in cosmetology, which is a very important element of its care and can decrease stress. Therefore, we believe that care and beauty treatments in combination with aromatherapy and music therapy can complement classical therapy. By reducing stress levels and improving the patient’s health, they can increase the quality of life.